The Role of Agentic AI and in Technology Access Enhancing MSME Competitiveness in the Digital Society - Candra; Maulana Habibi (Edusight International Journal of Multidisciplinary Studies, 2026)
The development of the digital society requires Micro, Small, and Medium Enterprises (MSMEs) to improve their technological adaptability in order to maintain business competitiveness. This study aims to analyze the role of Agentic AI and technology access in supporting the digital transformation of MSMEs in the digital economy era. The research employed a quantitative approach using multiple linear regression analysis with IBM SPSS Statistics involving 300 MSME respondents. The results indicate that Agentic AI and technology access have a positive and significant effect on MSME competitiveness. The simultaneous test (F-test) produced an F-value of 86.742 with a significance value of 0.000 < 0.05, indicating that the research model is feasible and statistically significant. The coefficient of determination (R²) value of 0.642 indicates that 64.2% of MSME competitiveness is influenced by Agentic AI and technology access, while the remaining 35.8% is affected by other factors outside the study. Partially, the Agentic AI variable obtained a t-value of 8.921 and technology access obtained a t-value of 6.754 with a significance value of 0.000, confirming that both variables significantly influence MSME competitiveness. The implementation of Agentic AI has been proven to improve operational efficiency, service quality, business productivity, and market expansion. However, technological implementation still faces challenges such as low digital literacy, limited human resources, technology adoption costs, and data security issues. Therefore, support from the government, private sector, and educational institutions is necessary to provide digital training, technological infrastructure, and supportive policies so that MSMEs can grow innovatively and competitively in the digital economy era.